CAPITAL BUFFERS AND LENDING DURING A CRISIS: CASE OF SERBIA - Martin, Vesna (Poslovna ekonomija, 2025)
Capital buffers ensure that banks will have the capacity to absorb any losses in the event of a financial crisis. Maintaining capital buffers at a high level enables banks to continue lending during times of crisis, protecting the stability of the financial system. On the other hand, banks may decrease lending activity in order to maintain capital adequacy if capital buffers are established at a low level, which could exacerbate the economic downturn. To guarantee economic recovery, it is therefore essential to find a balance between establishing and maintaining financial stability and credit activity during times of crisis. The capital buffers that banks in the Republic of Serbia have been required to set aside since Basel III was implemented will be analyzed in this paper along with an examination of the lending activity trend during times of crisis, including the coronavirus pandemic, the energy crisis, high inflation, and significant geopolitical tensions. As loan activity recovered, the research revealed that the Republic of Serbia’s banking sector kept adequate capitalization during periods of severe crisis.